Information driven entrepreneurship: A competitive intelligence approach. Issue 3 (3rd July 2022) - Olayemi, Olalekan Moses; Yacob, Haliso; Olayemi, Kemi Jummai
Abstract: At present, there is an increasing concern about the dearth of white-collar job opportunities for many recent graduates of tertiary institutions in Nigeria, including graduates of Library and Information Science (LIS) programmes. Hence, there is a need for LIS professionals to proactively explore ways to create jobs based on their professional skills and knowledge, rather than wait to be employed. This paper identifies and discusses areas of information driven entrepreneurial opportunities available for LIS professionals in Nigeria and highlights how competitive intelligence could be applied as a strategic tool to start their own businesses by putting LIS skills into practice. It also highlights the necessary skills required for entrepreneur startup and its sustainability as well as the benefits of being a librapreneur.